2021
DOI: 10.3390/ijerph182010600
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Resilience among Children Exposed to Non-Maltreatment Adverse Childhood Experiences

Abstract: Considering the high prevalence and negative consequences of non-maltreatment adverse childhood experiences (NM-ACEs), it is critical to understand their impacts on the resilient functioning of young children. This study sought to examine heterogeneity in resilience among first-grade children who were exposed to NM-ACEs during kindergarten and explore demographic and adversity characteristics that distinguish between resilience profiles. Latent profile analysis (LPA) was conducted on 4929 children drawn from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
(76 reference statements)
1
4
0
Order By: Relevance
“…The self-healing group, as the second-largest cluster, was characterized by severe PN and moderate-to-severe EN in combination with a moderate level of resilience. This finding is in line with previous studies that a relatively higher level of traumatic exposure was related to a relatively higher level of resilience (Osório et al, 2017), and the adaptive and resilient profile is the most prevalent profile among children and youth exposed to adverse childhood experiences (McDonald et al, 2016; Yoon et al, 2021). This finding supported the resilience framework that individuals can develop strength and resilience from adversities if they can deal satisfactorily with challenges.…”
Section: Discussionsupporting
confidence: 92%
“…The self-healing group, as the second-largest cluster, was characterized by severe PN and moderate-to-severe EN in combination with a moderate level of resilience. This finding is in line with previous studies that a relatively higher level of traumatic exposure was related to a relatively higher level of resilience (Osório et al, 2017), and the adaptive and resilient profile is the most prevalent profile among children and youth exposed to adverse childhood experiences (McDonald et al, 2016; Yoon et al, 2021). This finding supported the resilience framework that individuals can develop strength and resilience from adversities if they can deal satisfactorily with challenges.…”
Section: Discussionsupporting
confidence: 92%
“…For example, Martinez-Torteya et al ( 41 ) have found that in early childhood, resilience played a protective role in maintaining positive adaptive and easy temperamental characteristics in children exposed to domestic violence, compared to their non-resilient counterparts ( 41 ). Furthermore, previous research suggested that resilient children enable positive adaptation despite maltreatment ( 44 ). Sattler and Gershoff also found that children in poverty who reached higher levels of resilience at entry to kindergarten exhibit similar academic achievement throughout elementary school as children not in poverty ( 45 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, there is a plethora of research on resiliency and protective factors that help support healthy development [9,10]. These studies provide empirical evidence that these children can achieve positive adaptation despite their maltreatment [11][12][13][14][15]. Moreover, a robust body of research has found that certain protective factors help mitigate the harmful effects of childhood maltreatment [16,17].…”
Section: Resilience In Children With a History Of Child Maltreatmentmentioning
confidence: 99%
“…The study identified five profiles of adaptation/competence, including consistent resilience (12.7%), consistent maladaptation (11.6%), posttraumatic stress problems (8.9%), school maladaptation/family protection (36.2%), and low socialization skills (30.6%) [25]. Other studies, not specifically focused on child maltreatment, explored resilience patterns among children who have experienced early adversities and trauma (such as exposure to intimate partner violence, poverty, or parental psychopathology), and these studies likewise identified four or five patterns of resilience [15,26].…”
Section: Measuring Resilience and Identifying Patterns Of Resiliencementioning
confidence: 99%
See 1 more Smart Citation